Answer:
23x = -115
Step-by-step explanation:
In the substitution method, you must solve for 1 variable in 1 equation to replace it in the other equation. For the system:
2x - 7y = 4
3x + y = -17
Solving for y in the second equation:
y = -17 - 3x
Replacing y in the first equation:
2x - 7(-17 - 3x) = 4
2x + 119 + 21x = 4
23x = -115
This is the new equation after use the substitution method.
Answer:
x=4 y=7
Step-by-step explanation:
When multiplying 3x by -2, you get -6x. -6x and 6x cross out. You're left with -2y=-2 and -2y=10.
15. = slope would be 7 and y-int would be -4
16. = slope would be -2/5 and y-int would be 0
17. = doesn’t have a y variable
slope intercept form is y=mx+b with the m being the slope and the b being the y-int. in some cases where the equation is not in this form you have to change it so it is in that form by using opposite operations
Answer:

Step-by-step explanation:
Let the consecutive even numbers be x,x+2,x+4, x+ 6, x+ 8 and x+10
So, the given condition is:
x+x+2+x+4+x+6+x+8+x+10 = 270
6x + 30 = 270
Subtracting both sides by 30
6x = 270 - 30
6x = 240
Dividing both sides by 6
x = 40
So,
First Number = x = 40
Second Number = x+2 = 40+2 = 42
Third Number = x+4 = 40+4 = 44
Fourth Number = x+6 = 40+6 = 46
Fifth Number = x+8 = 40+8 = 48
Sixth Number = x+10 = 40+10 = 50